Screening is associated with a lower risk of hepatocellular carcinoma-related mortality in patients with chronic hepatitis B - Su, Feng (J Hepatol, 2020)
BACKGROUND AND AIMS: Patients with chronic hepatitis B (CHB) infection routinely undergo screening for hepatocellular carcinoma (HCC), but the efficacy of screening remains unclear. We aimed to evaluate the impact of screening with ultrasound (USS) and/or serum alpha-fetoprotein (AFP) on HCC-related mortality in patients with CHB. METHODS: We performed a matched case-control study of patients with CHB receiving care through the Veterans Affairs (VA) health administration. Cases were patients who died of HCC between 01/01/2004 and 12/31/2017, while controls were patients with CHB who did not die of HCC. Cases were matched to controls by CHB diagnosis date, age, sex, race/ethnicity, cirrhosis, antiviral therapy exposure, hepatitis B e antigen status, and viral load. We identified screening USS and AFPs obtained in the 4 years preceding HCC diagnosis in cases and the equivalent index date in controls. Using conditional logistic regression, we compared cases and controls with respect to receipt of screening. A lower likelihood of screening in cases corresponds to an association between screening and reduced risk of HCC-related mortality. RESULTS: We identified 169 cases, matched to 169 controls. Fewer cases than controls underwent screening with either screening modality (33.7% versus 58.6%) or both modalities (19.5% versus 34.4%). In multivariable conditional logistic regression, screening with either modality was associated with a lower risk of HCC-related mortality (adjusted odds ratio [aOR] 0.21, 95% confidence interval [CI] 0.09–0.50), as was screening with both modalities (aOR of 0.13, 95% CI 0.04–0.43). CONCLUSIONS: HCC screening was associated with a substantial reduction in HCC-related mortality in VA patients with CHB.